Association of provisional driver licensing intervention by police with changes in incidence and severity of road traffic injuries in Iran - Ainy, E; Soori, H; Nasermoadeli, A; Movahedi, M; Mehmandar, M R; Mahfozphoor, S; Masoodeinejad, M R; Hatamabadi, H R; Azari, M Rezazadeh; Vafaee, R (Injury prevention, 2010)
Objective This study was conducted to evaluate the role of provisional driving license implemented by the traffic police of Iran on reducing the incidence and severity of road traffic injuries. Methods It was a before-after interventional study. Data on road traffic crashes and injuries from 1 year before, 1 and 2 years after the implementation of provisional driver licensing were obtained from the traffic police database. After data cleaning and stratification of traffic injuries and mortalities, the implementation of graduate driver licensing compared in those in early years of their driving experience. Results Drivers under 23 years of age consisted 22.8% of total road traffic injuries (RTIs) in the year prior to the implementation of graduate driver licensing. This proportion reduced to 15.5% and 16.1% in the first and second year after the intervention, respectively, among holders of provisional B1 type driving license (p<0.001). Conclusion This intervention was effective in reduction of number and intensity of traffic injuries. Young and novitiate drivers are at high risk of RTIs. Provisional driving license program might be a key factor to reduce the incidence and severity of road traffic injuries among them.